Implementasi Soft Skill Guru Bahasa Arab Dalam Membentuk Kecerdasan Spritual Siswa MA NS Wanasaba Lombok Timur - Zakaki (Al-Faizi : Jurnal Politik, Hukum dan Bisnis, 2023)
Teacher soft skills are inter-personal and intra-personal skills in a teacher who can develop and maximize their performance in building relationships, teamwork, decision making, initiative, and communication so that these soft skills can shape the spiritual intelligence of students at school. This study aimed to determine the implementation of the teacher's soft skills in shaping students' spiritual intelligence. This study uses a qualitative approach and the type of research is descriptive. Researchers used the method of observation, interviews, and documentation in collecting data. Data is analyzed in several steps; reducing data, presenting data, and conclusions. The results of this study indicate that the implementation of the soft skills of Arabic language teachers in shaping the spiritual intelligence of students is carried out in several ways: a) Instilling religious values through integrative learning such as Arabic language subjects are integrated with Civics or civics subjects, b) Building harmonious communication such as communicating in polite, gentle, not harsh and harsh language, c) Establishing cooperation with all school members with the aim of producing output that is pious, noble, intelligent and skilled, d) Establishing cooperation with parents of students such as involving students to practice directly with learning study objects such as the practice of prayer, zakat, pilgrimage, distribution of inheritance, practicing the noble qualities of the companions of the Prophet, and other Islamic figures who have loyalty to Islam, e) Exemplary Approach, f) Strengthening through habituation is like getting used to planting and religious values in oneself and students, so as to maximize the spiritual intelligence of students, the hearts and feelings of students directly.